Preparation and properties of modified aluminum diethylphosphinate flame retardant for low‐density polyethylene. Issue 19 (16th December 2020) - Liu, Ben; Xu, Jiacheng; Xue, Honglai; Shu, Zhongjun; Xu, Guoguang; Ou, Hongxiang; Weng, Yunxuan
Abstract: To improve the flame retardancy of low‐density polyethylene (LDPE) and mechanical properties of LDPE composites, phenol‐formaldehyde aluminum diethylphosphinate microcapsules (PF@ADP) was prepared by in‐situ polymerization with phenol‐formaldehyde (PF) resin as the wall material and halogen‐free flame‐retardant aluminum diethylphosphinate (ADP) as the core material. The effects of PF@ADP on flame retardancy and mechanical properties of LDPE were investigated by methods of combustion experiments, mechanical analysis, thermogravimetric analysis (TGA), and smoke density analysis. The results indicated that, compared with ADP/LDPE composites, the flame retardancy and mechanical properties of PF@ADP/LDPE were obviously improved. With the addition of 20 wt% PF@ADP (PF:ADP = 3:7), the limit oxygen index (LOI) of LDPE composites increased to 30.7% and UL‐94 reached V‐1 grade. The tensile strength and elongation at break reached 12.5 MPa and 431.2%, which was 20.2% and 23.1% higher than that of ADP/LDPE with the same addition. The addition of PF@ADP was beneficial to the smoke suppression of LDPE. Abstract : In order to improve the flame retardancy of low‐density polyethylene (LDPE) and mechanical properties of LDPE composites, phenol‐formaldehyde aluminum diethylphosphinate microcapsules (PF@ADP) was prepared by in‐situ polymerization with phenol‐formaldehyde (PF) resin as the wall material and halogen‐free flame‐retardant aluminum diethylphosphinate (ADP) as the core material.